Increasing Parenting Capacity for Caregivers at the ‘Aisyiyah Sidoarjo Orphanage: Peningkatan Kapasitas Pengasuhan pada Pengasuh di Panti Asuhan Yatim ‘Aisyiyah Sidoarjo - Widyastuti; Fahmawati, Zaki Nur; By Arifin, Moch. Bahak Udin (Procedia of Social Sciences and Humanities, 2022)
Professional orphanage services are one of the standards in the accreditation of Social Welfare Institutions (LKS). The Aisyiyah Sidoarjo Orphanage as an LKS has the desire to provide the best service. Being an accredited orphanage does not mean that the management of the orphanage goes without obstacles. The identified partner problem is the lack of understanding and skills of caregivers in assisting foster children. The lack of quality of care is identified as one of the triggers for maladaptive behavior in foster children. Parenting capacity in question is an understanding of the character of foster children and skills in solving foster children's problems. The methods used to solve partner problems consist of, 1) Child and Adolescent Development Psychoeducation, and 2) Feedback Training Using Situation-Behavior-Impact (SBI) Techniques. The two activities were carried out on two different days with 11 caregivers and companions from the three 'Aisyiyah Sidoarjo Orphanages, namely Celep, Balongbendo, and Taman. As a result, the understanding of caregivers and companions on the character of foster children increased from 38% to 57%.